Implementasi Prinsip Washathiyah dalam Kontrak Bisnis Syariah: Perspektif Al-Qur'an - Wirman Wirman; Mustapa Mustapa (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to analyze the implementation of the washathiyah principle in Islamic business contracts from the perspective of the Qur’an, as well as to identify the obstacles that arise in practice. This research is classified as qualitative library research. The methodology combines a normative–theological approach with conceptual analysis of the washathiyah principle in Islamic business contracts. The findings indicate that the washathiyah principle is reflected in several components of Islamic contracts, such as mechanisms of information transparency, fairness in price determination, and proportional risk-sharing among the parties. Nevertheless, its implementation has not been fully consistent, as it is still influenced by limited sharia literacy, weak ethical business oversight, and the dynamics of the modern market, which often encourage practices that are not aligned with the values of moderation. Therefore, strengthening sharia education, improving the quality of regulation, and internalizing washathiyah values are essential steps toward realizing more just and sustainable Islamic business contracts.